Outcome and safety comparison of low-molecular-weight heparin versus unfractionated heparin for bridging anticoagulation in individuals with mechanical heart valves undergoing non-cardiac surgery: A systematic review and meta-analysis - Bhargah, Agha; Narayana, Gede S.; Maliawan, Rani PI.; Wirawan, Hendy; Darma, I KSS.; Artha, I MJR.; Manuaba, Ida BAP. (Narra J, 2025)
In patients with mechanical heart valves, low-molecular-weight heparin (LMWH) and unfractionated heparin are commonly used as bridging anticoagulation therapies to reduce the risk of thromboembolic events and major adverse cardiac events; however, the efficacy and safety of these therapies remain debatable. The aim of this study was to compare the safety and outcomes of LMWH and unfractionated heparin in patients with mechanical heart valve replacement undergoing non-cardiac surgery. This systematic literature review was conducted from January to June 2023, following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines to search for related studies through PubMed, ScienceDirect, and Cochrane Library. Categorical variables were analyzed using a Mantel-Haenszel random-effects model, with relative risk (RR) as the effect size. Higgins I2 was used to measure the heterogeneity and publication bias was assessed through funnel plots. Out of 814 potential studies, six studies (one randomized control trial and five prospective studies) were included. The analysis revealed no significant differences in thromboembolic event or valvular thrombosis (RR: 0.61; 95%CI: 0.36–1.04; p=0.07; ꭓ2=1.96; I2=0%), all-cause mortality (RR: 0.73; 95%CI: 0.40–1.35; p=0.32; ꭓ2=0.97; I2=0%), major bleeding (RR: 0.81; 95%CI: 0.53–1.23; p=0.33; ꭓ2=4.14; I2=0%), minor bleeding (RR: 1.18; 95%CI: 0.86–1.62; p=0.31; ꭓ2=4.50; I2=11%), and thrombocytopenia (RR: 0.56; 95%CI: 0.20–1.59; p=0.27; ꭓ2=0.85; I2=0%). The study highlights that LMWH and unfractionated heparin did not differ significantly when used as bridging anticoagulant therapy for non-cardiac surgery in mechanical heart valve patients.